2014
DOI: 10.1002/ange.201310539
|View full text |Cite
|
Sign up to set email alerts
|

Rhodium(II)‐Catalyzed Nondirected Oxidative Alkenylation of Arenes: Arene Loading at One Equivalent

Abstract: A bimetallic Rh II catalyst promoted the C À H alkenylation of simple arenes at 1.0 equivalent without the use of a directing group. A phosphine ligand as well as cooperative reoxidation of Rh II with Cu(TFA) 2 and V 2 O 5 proved essential in providing monoalkenylated products in good yields and selectivities, especially with di-and trisubstituted arenes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…This challenge is illustrated by the very limited reports on transition-metal-catalyzed C-H functionalization with arene as the limiting reagent. [43][44][45][46][47][48][49][50][51] In 2017, Yu and coworkers reported a palladium (Pd)catalyzed, pyridone-ligand-enabled Fujiwara-Moritani olefination reaction with arenes as limiting reagent. 43 Shortly thereafter, van Gemmeren reported the same transformation using a combination of a pyridine ligand and a mono-N-protected amino acid (MPAA) ligand.…”
Section: The Bigger Picturementioning
confidence: 99%
“…This challenge is illustrated by the very limited reports on transition-metal-catalyzed C-H functionalization with arene as the limiting reagent. [43][44][45][46][47][48][49][50][51] In 2017, Yu and coworkers reported a palladium (Pd)catalyzed, pyridone-ligand-enabled Fujiwara-Moritani olefination reaction with arenes as limiting reagent. 43 Shortly thereafter, van Gemmeren reported the same transformation using a combination of a pyridine ligand and a mono-N-protected amino acid (MPAA) ligand.…”
Section: The Bigger Picturementioning
confidence: 99%
“…As aresult of these studies,avariety of synthetic methods mostly based on Ir-a nd Rh-catalysis has been reported, which have proven particularly useful for late-stage C À heteroatom bond formation. [5,6] In contrast, Pd-catalysis has remained underdeveloped and until recently no general methods were available that allowed for the arene-limited nondirected formation of arylpalladium species.…”
Section: Introductionmentioning
confidence: 99%
“…Such mononuclear rhodium complexes have been proposed as plausible intermediates in the whole catalytic cycle, although their re-dimerization has not been considered . However, when weak bulky monodentate ligands are used in the reaction, monomerization is unlikely to occur because of the insufficient coordination of the rhodium center by the ligands owing to strong repulsion …”
Section: Introductionmentioning
confidence: 99%